IMPROVING THE COORDINATION ABILITIES OF STUDENTS AT A PEDAGOGICAL UNIVERSITY WITH THE USE OF BOXING TOOLS - Azizbek Jurayev (Bright Mind Publishing, 2025)
This article discusses the introduction of a set of exercises with boxing tools and elements during physical education training sessions with students of a pedagogical university, in order to increase their coordination abilities. 40 first-year students took part in the pedagogical experiment.
Keywords: Physical education, boxing, coordination abilities, dexterity, educational and training process, pedagogical experiment.